A fixed-size batch service queue with vacations. (1996) - Lee, Ho Woo; Lee, Soon Seok; Chae, K. C.
Abstract : The paper deals with batch service queues with vacations in which customers arrive according to a Poisson process. Decomposition method is used to derive the queue length distributions both for single and multiple vacation cases. The authors look at other decomposition techniques and discuss some related open problems.